An inventory optimization model for reliable and sustainable supply chains under trade credit and carbon constraints - Ankur Saurav; Vijender Yadav; Chandra Shekhar (Supply Chain Analytics, 2025)
The adoption of environmentally sound supply chain management strategies is gaining prominence in response to increasing sustainability efforts in emerging economies. As global environmental degradation escalates, industries are compelled to replace conventional products with green and reliable alternatives. This research introduces a dual-objective strategy aimed at minimizing operational costs while ensuring environmental preservation, focusing on identifying optimal approaches for production firms to achieve cost reduction alongside sustainability within the supply chain. It enables strategic insights in supply chain management to optimize inventory decisions, enhance financial adaptability, and ensure environmental compliance while maintaining profitability and reliability. Additionally, the study examines the impact of a two-level trade credit policy for a supplier-manufacturer-customer supply chain across nine scenarios based on credit periods. Four key contributions include (i) the evaluation of product greenness, reliability, price, and advertising on demand and deterioration rates; (ii) the analysis of reliability’s effect on production systems; (iii) the assessment of green technologies and cap-and-tax policies in emissions reduction; and (iv) the exploration of a partial two-level trade credit policy within a reliable production-based supply chain framework. The objective is to determine optimal investments in green technology, production run time, and cycle time to minimize total system costs, supported by numerical examples and graphical illustrations, offering insights for sustainable supply chain development in emerging economies.